'URF and its influence in determining islamic legal rulings on food related issues in Malaysia - Ruzulan, Zulaipa (2015)
There is a positive development in the halal food industry due to increasing market demand, as well as the advance of science and technology. This however, results in Shariah issues where the need arises for the clarification of Islamic legal rulings through ijtihadic process, for the reason that clear legal rulings in the Quran and Sunnah are limited. At this point, ʿurf is seen as one of the best sources to answer the arisen issues. Thus, the main objective of this study is to understand the concept of ʿurf and its influence in determining the legal status of food-related issues in Malaysia. In order to achieve this objective, a qualitative research method has been adopted where document analysis as well as in-depth interview were used. For documents analysis, the Holy Quran, hadith, classical manuals, contemporary literatures on Islamic law, government officials‟ documents, journal articles and other reliable websites were sought as they provide a range of rich data on the concept of ʿurf and its position in Malaysia, particularly vis-à-vis halal food related issues. Furthermore, in-depth interview was carried out, with over 15 key informants ranging from authoritative personnel and academicians selected to examine the influence of ʿurf in determining the legal rulings on food-related issues. The study has shown that the concept of ʿurf could be understood as a reality occurring during the particular time, where not only entails the changing of traditions that are accepted among general Muslim society, but also includes scientific facts that are recognized during the time. Moreover, the perception towards the characteristics of al-ṭayyibāt is not only limited to the ʿurf al-Arab, but is also actually based on ʿurf at a particular place; inclusive of the scientific ʿurf. The study also found that ʿurf does influence in the decision of the fuqahāʾ in dispensing legal rulings in foodrelated issues in Malaysia either on the state or federal level. This is proven through the study of ʿurf ijtimāʿī and ʿurf ʿilmī. As far as ʿurf ijtimāʿī is concerned, all key informants have agreed on its authoritativeness and otherwise, while almost half of informants agree on the authoritativeness of ʿurf ʿilmī. The remainder disagrees due to differentiation between ʿurf, and science, and technology. Moreover, the study also further identified that both types of ʿurf have influenced the fuqahāʾ in determining the legal rulings on food related issues where if there is valid evidence from the scientific community, the ʿurf ʿilmī prevail. However, if the scientific evidence is found to still be in a stage of theoretical probability or there is no scientific evidence, ʿurf ijtimāʿī therefore influences the conclusion of legal rulings. It is hoped that this study will benefit both policy makers as well as food practitioners especially when it comes to issues of legal rulings in the food industry. It is also suggested that experts in food are included in fatwa committee meetings so as to assist the fuqahāʾ in deducing legal rulings that conform to reality.